Optimization of Annealing Temperature and Agarose Concentration in Detecting the mecA Gene of Methicillin-Resistant Staphylococcus aureus (MRSA) - Muhammad Abdullah Alhakim; Kurnia Ritma Dhanti; Kurniawan Kurniawan; Arif Mulyanto (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Methicillin-resistant Staphylococcus aureus (MRSA) is associated with the expression of the mecA gene. This study aimed to determine the optimal annealing temperature and agarose concentration to achieve the best PCR product quality based on the evaluation of DNA band integrity, thickness, and resolution. DNA was extracted from five S. aureus samples to detect isolates containing the mecA gene. The experimental variations included annealing temperatures of 53°C, 55°C, 57°C, and 59°C, as well as agarose concentrations of 1% and 1.5%. Through densitometry measurements, the optimal mecA gene band thickness was achieved at an annealing temperature of 59°C. Furthermore, the use of a 1.5% agarose concentration provided the best DNA separation resolution compared to the 1% concentration. In conclusion, optimization of annealing temperature and agarose concentration parameters was crucial to ensure the accuracy of MRSA diagnosis in the laboratory .